2020
DOI: 10.1021/acsinfecdis.9b00365
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenic Streptococcus mutans Produces Tetramic Acid Strain-Specific Antibiotics That Impair Commensal Colonization

Abstract: Streptococcus mutans is a common constituent of dental plaque and a major etiologic agent of dental caries (tooth decay). In this study, we elucidated the biosynthetic pathway encoded by muc, a hybrid polyketide synthase and nonribosomal peptide synthetase (PKS/NRPS) biosynthetic gene cluster (BGC), present in a number of globally distributed S. mutans strains. The natural products synthesized by muc included three N-acyl tetramic acid compounds (reutericyclin and two novel analogues) and an unacylated tetrami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(109 citation statements)
references
References 30 publications
10
99
0
Order By: Relevance
“…These bacteria have been shown to produce structurally diverse NPs with potent bioactivities. [29][30][31][32][33] The antimicrobials from Nocardia spp. and bacteriocins from Staphylococcus spp.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…These bacteria have been shown to produce structurally diverse NPs with potent bioactivities. [29][30][31][32][33] The antimicrobials from Nocardia spp. and bacteriocins from Staphylococcus spp.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…66,67 Several bioactive NPs have recently been isolated from S. mutans. 30,[68][69][70][71][72][73][74][75][76][77][78] Vibrionaceae includes several species that cause intestinal (diarrhoea, cholera) and extra-intestinal (septicaemia, skin infection) illnesses in both humans and aquatic animals. Among the opportunistic Vibrio pathogens, V. parahaemolyticus has been shown to produce metabolites with remarkable bioactivity.…”
Section: Human and Animal Pathogenic Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, genomic analysis of various S. mutans isolates demonstrated that these facultative anaerobes collectively harbored a plethora of biosynthetic gene clusters (BGCs) for polyketide/non-ribosomal peptide biosynthesis [14][15][16] . Some of the associated products were also reported, including mutanobactin with an inhibitory activity against the morphological transition of Candida albicans 17,18 , mutanocyclin that suppressed the infiltration of leukocytes 19 , and reutericyclin that inhibited the growth of oral commensal bacteria 20 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 96%